Antibacterial Effectiveness Test Against Staphylococcus Aureus Bacteria in Periodontal Dressing Zoe With and Without Chitosan BSF (Black Soldier Fly) - Andi Supriatna; Saskia Lenggogeni Nasroen; Aisyah Putri Rahayu (Universitas Pahlawan Tuanku Tambusai, 2025)
Periodontal dressings has an important role in reducing the risk of infection and assisting in the wound healing processed after periodontal surgery. One of the materials used is ZOE-based. BSF chitosan is one of the ingredients that can be added to periodontal dressings. Periodontal dressing must have antibacterial properties, to increased effectiveness during the healing process. This study aims to determine whether there is antibacterial effectiveness against Staphylococcus aureus bacteria in ZOE periodontal dressing with and without BSF chitosan. Antibacterial testing was carried out using the well diffusion method with test groups using the ZOE control group, ZOE with 10% and 20% BSF chitosan. The results was analyzed using the Shapiro Wilk test, Levene test, One Way Anova followed by the Post Hoc Tukey HSD test (p>0.05). The results shows that ZOE periodontal dressing with and without BSF chitosan has antibacterial effectiveness in each treatment, but there is no significant difference between each group.